role of tools promotional mix in sales growth - الكعبي نعمة شليبة; اللامي شهلاء علي (Journal of Economics and Administrative Sciences, 2018)
The mix promotion important to any organization in general, has been selected promotional mix tools in this research to identify the role in maximizing the Organization of sales growth business, which included the research problem several fundamental questions about the role of each promotional tool of advertising, public relations and personal selling and sales promotion direct marketing within the promotional mix in the promotion of business sales organization. The research aims to provide theoretical and field organizations surveyed about the role played by the mix promo in sales growth, and importance of research on the identification of more than promotional tools impact on sales growth through the statement of a relationship of the lack thereof and the statement of strength of the relationship in the case of its existence, was the data using collection questionnaire form distributed to the research community of companies contact (Zain and Asiacell Telecom) was the sample of managers and their assistants by 70 individuals and the statistical methods used to search included distributions repeatability and relative circles calculations, standard deviation and correlation coefficient and. Using a computerized program SPSS. The research was based on major premise is no statistically significant correlation between the promotional mix and growth of the company’s sales relationship,. The most significant results rise evened the awareness of individuals under consideration of the importance of every tool of promotion mix tools, it is clear that the communications companies surveyed largely concerned with the announcement and personal selling, direct marketing to promote their products in the market and try to expand its sales, development of the surveyed services contact companies that offer to their customers so as to maximize sales , and trends in the field of communications companies to increase their sales focus on the entry of new parts for the current market and this means that the current market (customers) tend to consume more and request communications services. And recommendations of the research that the intensity of competition at the moment and the evolution of the needs and desires of customers have made customers point that underpin the company to identify trends, which requires the support of promotional mix elements in order to create value for customers, and work on the use of direct communication between the company and its customers by publishing direct contact centers in areas where the company resides customers need to do to train marketing and promotional staff who care about the needs of the target customers and their wishes and interact with him to achieve effective communication fruitful in this area